IMPLEMENTASI SISTEM PRESENSI BERBASIS IOT (INTERNET OF THINGS) MENGGUNAKAN PLATFORM BLYNK DI SMK CENDIKIA RANCAKALONG - Jupriyanto, Jupriyanto; Maulana, Lutfi; Udoyono, Kodar; Permana, Eka (Jurnal Teknologi Informasi dan Komunikasi, 2024)
An IoT (Internet of Things) based attendance system using the Blynk Platform with NodeMCU and ESP32-CAM is a teacher attendance management and monitoring system. This system combines Radio Frequency Identification (RFID) technology for time and attendance detection, NodeMCU and ESP32-CAM microcontroller hardware for data processing, and a MySQL database for storage and management of time and attendance data. Using an RFID card, teachers can easily record attendance via a reader connected to the NodeMCU, and the ESP32-CAM provides the ability to capture facial images as an additional verification step. Attendance data is stored in a MySQL database in a structured manner, enabling efficient data management and accurate attendance reporting.